Preliminary Study of Cultural-Based Empathic Support to Reduce Perceived Stigma for Covid-19 Survivors and Families - ridhoi meilona purba; Ari Widiyanta Widiyanta; Anna Kasfi Kasfi (Analitika: Jurnal Magister Psikologi UMA, 2022)
This study aims to explore appropriate and meaningful forms of cultural-based support to support the recovery of COVID-19 survivors and the psychological well-being of families who are still vulnerable to receiving social stigma from society. The research method used is qualitative, which is carried out on respondents from religious practitioners, cultural practitioners, and psychologists who have direct experience with the community. The results of this study are expected to be used as guidelines for psychological treatment that can be used by related parties such as hospitals, educational institutions, the government and the private sector to accelerate the recovery process for Covid-19 survivors and their families. The results showed that: 1). Culture plays a very important role in providing social stigma and also in dealing with stigma itself; 2) Several cultural-based support practices are carried out to restore psychological conditions; 3) Empathic support which focuses on understanding the thoughts and feelings of survivors and families in their own perceptions is a concern in culture-based support practices. This study concludes that the practice of culturally based empathy support is meaningful to reduce and prevent the stigma felt by Covid-19 survivors and their families.